Improvement of the Biosynthesis of Resveratrol in Endophytic Fungus (Alternaria sp. MG1) by the Synergistic Effect of UV Light and Oligomeric Proanthocyanidins - Lu, Yao; Shi, Junling; Zhao, Xixi; Song, Yuyang; Qin, Yi; Liu, Yanlin (Frontiers in Microbiology, 2021)
Resveratrol, a natural polyphenol compound with multiple bioactivities, is widely used in food and pharmaceutical industry. Endophytic fungus Alternaria sp. MG1, as a native producer of resveratrol, shows increasing potential application. However, strategies for improvement of the biosynthesis of resveratrol in this species are still scarce. In this study, different elicitors were used to investigate their effect on the biosynthesis of resveratrol in MG1 and the induction mechanism. Ultrasound and sodium butyrate had no effect and slight inhibition on the resveratrol production and related gene expression, respectively. UV radiation and co-culture with Phomopsis sp. XP-8 significantly promoted the biosynthesis of resveratrol with the highest production (240.57 μg/L) coming from UV 20 min. Co-culture altered the profiles of secondary metabolites in MG1 with the increase of stilbenes, completely inhibition of lignins, and new generation of flavonoids. Oligomeric proanthocyanidins (OPC) also showed an obviously positive influence, leading to the resveratrol production of 255.01 μg/L. Two calmodulin-dependent proteins (CDPK) were identified, of which CDPK1 was found to be an important regulatory factor of OPC induction. Synergistic treatment of UV 20 min and 100 μM OPC increased the production of resveratrol by 70.37% compared to control, and finally reached 276.31 μg/L.